Twentieth-Century Greek Cypriot Art: An “Other” Modernism on the Periphery - Danos, Antonis (My University, 2014)
Twentieth-century Cypriot art, from its emergence within the conditions of colonialism to its flowering in the post-independence era, constitutes a case of an “other” modernism on the periphery. It was a “site-specific” modernism that responded to particularities of Cyprus’s experience of modernity. With regard to Greek Cypriot artists in particular, these responses included a varied negotiation of tradition as well as of modern art as part of both the need to define a collective identity for the colonial moment and the process of achieving a post-colonial present and future. The works of Adamantios Diamantis, Georghios Pol. Georghiou, and Christoforos Savva—three of the most prominent modern Cypriot artists—constitute important episodes in the course of Cypriot modernity, especially in the middle decades of the century. Taken together, their artistic oeuvres chart the trajectory of Greek Cypriot modernism in the pre-1974 era, the mapping of which contributes to the discourse of “alternative” instances in the history of modern art.